SOSIALISASI DAN PELATIHAN SMART PARKING SISTEM BOOKING IOT BERBASIS ANDROID DI SMKN 2 PALEMBANG - Mohammad Fadhli; Lindawati; Soim, Sopian Soim (Politeknik Negeri Sriwijaya, 2024)
The increasing use of vehicles in big cities, including at SMK Negeri 2 Palembang, results in significant challenges in parking management, such as congestion and inconvenience due to conventional systems. Therefore, efficient parking management is required. One solution to overcome these challenges is to utilize Internet of Things (IoT) technology. A smart parking system based on IoT and Android is a crucial solution in overcoming parking management problems in urban areas. Through socialization conducted at SMK Negeri 2 Palembang, this activity aims to provide students and teachers with an understanding and skills regarding IoT technology in effective parking management. The socialization included basic theoretical presentations on IoT and Android technology, as well as practical demonstrations of how the smart parking system works. The participants were trained to understand the components of the system, such as IR sensors, Arduino Mega 2560, and mobile applications, and were involved in hands-on system testing practices. The results of the socialization showed that the participants understood how the system worked and could perform simple practices of sending sensor data using an IoT server.